Physical therapists' experiences and perceptions of antepartum and postpartum care - Kuan-Yin Lin; Yi-Ju Tsai; Jeng-Feng Yang; Meng-Hsing Wu (BMC, 2022)
Abstract Background Little is known about the physical therapists' practice and perceptions toward management of pregnancy/postpartum-related disorders in Taiwan. The aim of this study was to document current practice of physical therapy in antepartum and postpartum care in Taiwan. Methods An exploratory, cross-sectional study was conducted in registered physical therapists living in Taiwan. An anonymized online survey was designed, piloted, and advertised widely from March 2020 to March 2021. Data were analyzed using descriptive statistics, Chi square analysis and multivariate logistic regression. Results Of the 364 respondents, 37.6% had experience of treating pregnant or postpartum women in clinical practice. The most commonly treated pregnancy/postpartum-related disorder in practice was low back pain (61.3%). All respondents reported little to moderate level of confidence in their ability to manage pregnancy/postpartum-related disorder. Being female (p < 0.01); working at a regional hospital (p = 0.01), district hospital or district teaching hospital (p < 0.01), clinic (p = 0.01) or physiotherapy clinic (p = 0.01); and having prior experience of treating antepartum or postpartum women (p < 0.01) were significantly associated with willingness to provide customer-oriented service or health education to patients/clients with pregnancy/postpartum-related disorder after controlling for other confounding variables. The most commonly reported barrier was "lack of available training" (81.3%). Conclusion The majority of participating physical therapists indicated a positive attitude to antepartum and postpartum care but were not confident in management of various pregnancy/postpartum-related disorder in practices. The findings of this study highlight the educational needs related to antepartum and postpartum care in clinical practice for physical therapists in Taiwan.